2010
DOI: 10.1080/07347332.2010.504504
|View full text |Cite
|
Sign up to set email alerts
|

Online Support Groups for Women with Metastatic Breast Cancer: A Feasibility Pilot Study

Abstract: This study evaluates the feasibility and acceptability of an online peer support group intervention for women with metastatic breast cancer (MBC). Feasibility, participation rates, participant satisfaction, and preliminary outcomes are examined from a 1999 to 2000 study of online peer support groups for women with MBC. Thirty women with MBC were randomly assigned to either an immediate online support condition or a waitlisted control condition. For practical and ethical reasons, the waitlist period was limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 61 publications
(78 reference statements)
0
41
0
5
Order By: Relevance
“…Some of the most promising projects used outcome measures that were associated only with the feasibility or usability of the intervention, an important first step in a complex intervention, but of little use in assessing clinical benefit [5,[23][24][25][26]29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most promising projects used outcome measures that were associated only with the feasibility or usability of the intervention, an important first step in a complex intervention, but of little use in assessing clinical benefit [5,[23][24][25][26]29,30].…”
Section: Discussionmentioning
confidence: 99%
“…As they did not have an objective outcome measure they did not fit the inclusion criteria for full analysis. Overall these studies demonstrated that the use of online interventions for support or therapy in this population was feasible to implement and acceptable to the recipients in a general sense [5,[23][24][25][26][27][28][29][30].…”
Section: Feasibility and Acceptability Studiesmentioning
confidence: 99%
“…A range of computer-mediated social support groups are developed to deal with various conditions including self-injury (Haberstroh & Moyer, 2012), Amyotrophic Lateral Sclerosis which is a progressive neurodegenerative disease that affects nerve cells in the brain and the spinal cord (Loanea & D'Alessandroa, 2013), suicidal individuals (Gilat, Tobin & Shahar, 2011), metastatic breast cancer (Vilhauer, McClintock & Matthews, 2010), issues related to membership of a stepfamily (Christian, 2005), and male infertility (Malik & Coulson, 2008). The benefits of computer-mediated social support groups are not only to accommodate the individuals suffering the illness/conditions but also the parents, family and carers.…”
Section: Computer-mediated Social Support Groupmentioning
confidence: 99%
“…Early efforts to measure engagement with Internet-based interventions used general engagement measures, such as number of messages posted [7, 10, 20-24], number of logins [7, 9, 24-26], number of page views [5, 27], and time on the study website [9, 24, 28, 29]. Number of logins is one of the most commonly reported types of engagement across Internet-based interventions for health [3032].…”
Section: Introductionmentioning
confidence: 99%
“…Number of logins is one of the most commonly reported types of engagement across Internet-based interventions for health [3032]. Among Internet-based interventions specific to cancer, average logins per week has been remarkably stable, ranging from 2.5 logins per week [24] to 2.9 logins per week [9, 25, 26]. Another marker of engagement is whether participants actively contribute, by posting messages or responses, to a study website.…”
Section: Introductionmentioning
confidence: 99%